LEADERSHIP STYLES AND ORGANIZATIONAL PERFORMANCE: ANALYZING THE IMPACT OF DIFFERENT LEADERSHIP STYLES ON THE OVERALL PERFORMANCE OF AN ORGANIZATION (Conferencea, 2023)
This research paper explores the relationship between leadership styles and organizational performance, aiming to analyze the impact that different leadership styles have on the overall performance of an organization. The paper investigates various leadership theories, such as transformational, transactional, autocratic, democratic, and laissez-faire leadership styles. It reviews and examines empirical studies and case studies that highlight the influence of these leadership styles on key performance indicators, including employee satisfaction, productivity, innovation, and financial performance. The findings of this paper contribute to a deeper understanding of the significance of leadership style in optimizing organizational performance and provide insights for organizational leaders to enhance their leadership strategies accordingly.